Intermediate Phase‐Free Process for Methylammonium Lead Iodide Thin Film for High‐Efficiency Perovskite Solar Cells. Issue 21 (17th September 2021) - Yun, Yeonghun; Vidyasagar, Devthade; Lee, Minho; Gong, Oh Yeong; Jung, Jina; Jung, Hyun‐Suk; Kim, Dong Hoe; Lee, Sangwook
Abstract: Solvent engineering by Lewis‐base solvent and anti‐solvent is well known for forming uniform and stable perovskite thin films. The perovskite phase crystallizes from an intermediate Lewis‐adduct upon annealing‐induced crystallization. Herein, it is explored the effects of trimethyl phosphate (TMP), as a novel aprotic Lewis‐base solvent with a low donor number for the perovskite film formation and photovoltaic characteristics of perovskite solar cells (PSCs). As compared to dimethylsulfoxide (DMSO) or dimethylformamide (DMF), the usage of TMP directly crystallizes the perovskite phase, i.e., reduces the intermediate phase to a negligible degree, right after the spin‐coating, owing to the high miscibility of TMP with the anti‐solvent and weak bonding in the Lewis adduct. Interestingly, the PSCs based on methylammonium lead iodide (MAPbI3 ) derived from TMP/DMF‐mixed solvent exhibit a higher average power conversion efficiency of 19.68% (the best: 20.02%) with a smaller hysteresis in the current‐voltage curve, compared to the PSCs that are fabricated using DMSO/DMF‐mixed (19.14%) or DMF‐only (18.55%) solvents. The superior photovoltaic properties are attributed to the lower defect density of the TMP/DMF‐derived perovskite film. The results indicate that a high‐performance PSC can be achieved by combining a weak Lewis base with a well‐established solvent engineering process. Abstract : A low defect halide perovskite film can be fabricated using trimethyl phosphate (TMP). TMP directly forms perovskite without intermediate phase due to weak Lewis basicity. The TMP‐based film reduces hysteresis in current‐voltage curve of perovskite solar cell. The TMP‐based device exhibits better performance (>20%) than other solvent‐based ones.